2011
DOI: 10.1590/s0100-204x2011001000021
|View full text |Cite
|
Sign up to set email alerts
|

Soil biological attributes in pastures of different ages in a crop-livestock integrated system

Abstract: -The objective of this work was to evaluate the effect of the pasture (Urochloa brizantha) component age on soil biological properties, in a crop-livestock integrated system. The experiment was carried out in a Brazilian savannah (Cerrado) area with 92 ha, divided into six pens of approximately 15 ha. Each pen represented a different stage of the pasture component: formation, P0; one year, P1; two years, P2; three years, P3; and final with 3.5 years, Pf. Samples were taken in the 0-10 cm soil depth. The soil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
7
0
6
Order By: Relevance
“…Nevertheless, research conducted in tropical soils in forest ecosystems in Latin America (PFENNING et al, 1992;GROFFMAN et al, 2001) and in the Brazilian Cerrado (CARNEIRO et al, 2008;ALVES et al, 2011;MUNIZ et al, 2011) demonstrate that, in some cases, a significant increase in SMB (C mic ) may occur in grazing areas, compared to similar soils under native vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, research conducted in tropical soils in forest ecosystems in Latin America (PFENNING et al, 1992;GROFFMAN et al, 2001) and in the Brazilian Cerrado (CARNEIRO et al, 2008;ALVES et al, 2011;MUNIZ et al, 2011) demonstrate that, in some cases, a significant increase in SMB (C mic ) may occur in grazing areas, compared to similar soils under native vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Esses resultados podem ser associados ao sistema radicular abundante presente nas pastagens, propiciando maior liberação de exsudatos (fonte de energia), com subsequente aumento da população de micro-organismos na rizosfera (Cunha et al, 2011). Por outro lado, a permanente cobertura do solo e a ausência de distúrbios provocados por práticas agrícolas, também contribuem para o aparecimento de condições favoráveis ao crescimento microbiano em pastagens do cerrado, conforme preconizado por alguns autores (Muniz et al, 2011). Em todos os sistemas verificou-se maior concentração da biomassa microbiana nas camadas superficiais decorrente da maior presença de matéria orgânica e raízes, consideradas fontes de energia para a microbiota do solo.…”
Section: Resultsunclassified
“…Referidos resultados foram maiores naqueles observados por Jakelaitis at al. (2008), que obtiveram, em área de pastagem de Brachiaria brizantha na camada de 0-10 cm em Minas Gerais, quociente microbiano de 0,91% e próximo dos observados por Muniz et al (2011) para a mesma espécie com 3 anos (3,3%) e com 3-5 anos (4,4%), na camada de 0-10 cm. Um estado de equilíbrio no quociente microbiano pode ser considerado quando os valores se situam entre 2 e 5, significando que 2 a 5% do solo é composto pelos micro-organismos e, sob este pressuposto, apenas no solo sob PAST, isto foi alcançado em todas as camadas.…”
Section: Resultsunclassified
“…Highly productive Brazilian Oxisols often have high levels of microbial biomass, associated with higher levels of soil organic matter, resulting in higher soil quality (Lopes et al, 2013). Muniz et al (2011) reported that the recovery of degraded pastures by implementing ICLS on Oxisols increased microbial biomass carbon (MBC), even when compared with native cerrado (Brazilian savanna vegetation). Similarly, Frazão et al (2010) showed that MBC and microbial biomass nitrogen (MBN) values may be higher or equivalent to those of native cerrado, in a Typic Quartzipsamment both under cultivated pasture [Urochloa decumbens (Stapf) R.D.Webster] and ICLS.…”
Section: Introductionmentioning
confidence: 99%